PENGAWASAN DAN DISIPLIN TERHADAP KINERJA PEGAWAI PADA BADAN PERENCANAAN PEMBANGUNAN DAERAH - Astuti Yulia Fitri; Sadikun Citra Rusmana (Jurnal Riset Bisnis dan Manajemen, 2020)
Supervision as one of the management functions in achieving goals, plays a very important role by monitoring the possibility of preventable deviations, then discipline is a tool used to communicate with employees so that they are willing to change behavior and as an effort to increase awareness and willingness to obey all company regulations and prevail social norms. The purpose of this study is to determine the responses of respondents and the influence of supervision, work discipline on employee performance at BAPPEDA Kota Bandung, simultaneously or partially. This research method is quantitative with multiple linear regression analysis techniques. The results showed consumer responses to supervision with a score of 3.73, discipline with a score of 3.76, and performance with a score of 3.77. There is as well as a positive and significant effect partially and simultaneously from supervision, discipline of employee performance at BAPPEDA Kota Bandung.